IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM PELAJARAN SEJARAH - Siti Nurbaya; Mahlaini Azizah Harahap; Mgs Hasrul Haris; Syarifuddin Syarifuddin; Rani Oktapiani (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
In the era of Society 5.0, history education faces a major challenge in the form of the stigma that it is a boring subject that focuses too much on memorization. This has an impact on low student engagement, both behaviorally, emotionally, and cognitively. In fact, 21st-century education requires a paradigm shift from teacher-centered learning to student-centered learning in order to develop critical thinking skills and historical awareness. Using library research methods through a qualitative approach, this study synthesizes four main models: Project-Based Learning, Problem-Based Learning, Gamification, and Inquiry-Based Learning. The results of the analysis show that PjBL is effective in building authentic experiences through concrete products, PBL hones analytical skills on historical issues, Gamification increases extrinsic motivation through game elements, and Inquiry encourages research independence. Although these models are significantly capable of activating students' behavioral, emotional, and cognitive participation, their implementation still faces challenges in the form of digital infrastructure gaps and limited teacher competencies. This study concludes that the adaptive combination of various innovative models is the key to transforming static historical narratives into relevant and collaborative learning processes for the 21st century generation